Poetics of names in Russian epics - N. Mitropolskaja (Literatūra (Vilnius))
Epos attaches great importance to poetics of names. Intelligent substantivity of names and its interpretation are connected with the ideas and images of heroic epos, with its artistic aim towards heroism and idealization of Russian epic heroes. Striving for understanding of Russian epics as poetical verbal creation evokes the necessity of studying the artistic value in the usage of names, their aesthetic function in Russian epic.The paper deals with the majestic and pet names, with slighting forms of proper names, with folk-etymological poeticization of names and denominations, with names of negative social reference that are attributed to the poetics of censure and mockery. Geographical denominations in Russian epic do not only locate the place of action but also express Motherland's theme in an image-bearing way and, as an artistic element, are part of the composition of hyperboles and epic formulative expressions.